Chromosome polymorphism and cytotype establishment in Bidens pilosa (Asteraceae) - Mariano, A. C.; Marin-Morales, M. A. [UNESP] (My University, 1999)
Chromosome evolution, in the Bidens genus, was by polyploidy mechanisms. The basic number to the genus is X = 12 chromosomes, as all the Fitchinae subtribe. The association of chromosome number and environment in these plants was made some time ago, concerning the cytotypes of the species. In this paper, the chromosome number of nine Bidens pilosa populations was studied. The chromosome numbers found were 2n = 48, 70 and 72. In six of the nine populations analysed the most frequent number was 2n = 72. The lbiúna population had 2n = 70 chromosomes and two had the lowest chromosome number (2n = 48). Observations of the B. pilosa population suggests that ploidy levels were related to a geographical gradient establishing the environmental altitudes. The data showed that lower ploidy levels, that is 2n = 48, were found at lower altitudes, while the populations higher ploidy levels were found in several environments, over a wide distribution.
Keywords: Bidens pilosa; Chromosome polymorphism; Cytotype; Karyotype; Plant cytogenetics